KARAKTERISASI DAN UJI AKTIVITAS Bacillus spp. SEBAGAI AGENSIA PENGENDALIAN HAYATI PENYAKIT LINCAT PADA TEMBAKAU TEMANGGUNG - Triwidodo Arwiyanto; YMS Maryudani; Agus Eko Prasetyo (JURNAL PENELITIAN BIOLOGI BERKALA PENELITIAN HAYATI, 2007)
Lincat disease of tobacco causing severe losses of the product. Control of the disease with any available measure unlikely giving enough control. A number of Bacillus spp. isolates could suppressed the growth of pathogen in vitro and suppressed the development of lincat disease in the field. This article report the characteristics of six isolates of Bacillus spp. (Ba-4, Ba-22, Ba-24, Ba-30, Ba-33, dan Ba-41). These isolates proven could suppressed lincat disease in the field. Characterization of the isolates include the morphological, physiological characteristics, and pathogenicity against tobacco plant. The results indicated that the bacterial isolates were belong to the genus Bacillus with the following charactheristics. The bacteria were rod shapes, forming endospore, Gram positive, fermentative, positive reaction in katalase, oksidase, and Voges Proskaeur tests. Negative results were obtained for Methyl Red test, hydrolysis of starch, gelatine, and casein. The present isolates could use citrate and several carbohydrates as carbon sources. Reduce nitrate to nitrite. The isolates could grow in the medium with high osmotic pressure, i.e. could grow in the medium with 7% NaCl. The present isolates grew well in the medium with pH of 4.5–10 and could grow in the temperature range of 10–50 °C. According to pathogenicity test, the present isolates were not belong to the plant pathogenic bacteria. The present isolates could suppressed the growth of Ralstonia solanacearum in vitro, and could reduce the egg number of Meloidogyne incognita. According to the physiological characteristics tested, it seem that isolates of Ba-4, Ba-24, Ba-30, dan Ba-33, and Ba-41 having similar charactheristics with Bacillus cereus. The Ba-22 isolate, however, having similar characteristics with B. licheniformis.